2019
DOI: 10.4103/aam.aam_11_18
|View full text |Cite
|
Sign up to set email alerts
|

Acute perforated appendicitis in adults: Management and complications in Lagos, Nigeria

Abstract: Background:Acute perforation of the appendix is one of the complications of appendicitis that is associated with increased morbidity and mortality and hence regarded as a surgical emergency. Risk factors for perforated appencidicits include extremes of age, male sex, pregnancy, immunosuppression, comorbid medical conditions and previous abdominal surgery.Objectives:This study focuses on the pattern of presentation, risk factors, morbidity and mortality of patients managed for perforated appendicitis in our cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
4
17
2
9
Order By: Relevance
“…Males have been reported present more often with perforated appendixes 16 However, in our study, no significant dominance of either gender was observed (p-value). There was no significant difference in age was also found in both age groups.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Males have been reported present more often with perforated appendixes 16 However, in our study, no significant dominance of either gender was observed (p-value). There was no significant difference in age was also found in both age groups.…”
Section: Discussioncontrasting
confidence: 83%
“…While this holds for all equivocal cases, authors believe that in all overt cases of peritonitis, early intervention might have a positive role in limiting postoperative SIRS. 16…”
Section: Discussionmentioning
confidence: 99%
“…Males have been reported present more often with perforated appendixes (16). However, in our study, no significant dominance of either gender was observed (p-value).…”
Section: Discussioncontrasting
confidence: 81%
“…The common complication of appendicitis could be the perforation, abscess formation and appendicular lump. 24 In our study, the patients' age ranged from 8 years to 76 years with mean age 35±15.6 with maximum incidence 87.4 % below 50 years. This result is nearly consistent with several studies that report 95 % appendicitis below 50 years age.…”
Section: Discussionmentioning
confidence: 70%